Systemic Violence, Subjectivity of Risk, and Protective Sociality in the Context of a Border City: Ciudad Juarez, Mexico - Salvador Salazar Gutiérrez (El Colegio de la Frontera Norte, A.C., 2014)
Using a sociocultural perspective to examine the context of systemic violence in the border city of Ciudad Juárez, this article analyzes a subjectivity of risk has been produced, based on an analysis of excerpts from interviews of social actors related to the fields of political, business, religious, and journalistic discursivenes.